2003
DOI: 10.1161/01.atv.0000098644.03153.6f
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor–Regulated Gene Expression in Endothelial Cells

Abstract: Objective— The program of gene expression regulated by vascular endothelial growth factor (VEGF) remains poorly understood. The aim of this study was to identify VEGF-regulated genes in human umbilical vein endothelial cells. Methods and Results— VEGF-regulated gene expression was analyzed by screening Affymetrix oligonucleotide arrays and quantitative, real-time, reverse transcription–polymerase chain reaction. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
94
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 152 publications
(100 citation statements)
references
References 41 publications
6
94
0
Order By: Relevance
“…VEGF is a pivotal mediator of this process, but while the array of endothelial genes upregulated by VEGF has been described (Abe and Sato, 2001;Liu et al, 2003), the role of individual gene functions regulated by VEGF is poorly understood. A previous study reported that inhibition of Egr1 protein expression by DNAzymes blocked serum-induced proliferation and migration and perturbed pre-existing tubular structures in Matrigel (Fahmy et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…VEGF is a pivotal mediator of this process, but while the array of endothelial genes upregulated by VEGF has been described (Abe and Sato, 2001;Liu et al, 2003), the role of individual gene functions regulated by VEGF is poorly understood. A previous study reported that inhibition of Egr1 protein expression by DNAzymes blocked serum-induced proliferation and migration and perturbed pre-existing tubular structures in Matrigel (Fahmy et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous findings demonstrated that FGF-2 also significantly upregulated Egr3 expression, but caused a much smaller increase in expression of the NR4A gene family (Liu et al, 2003). The induction of Egr3 by FGF-2, although weaker than that of VEGF ( Figure 3a), prompted us to also examine the effects of Egr3 siRNA on the biological response to FGF-2.…”
Section: Vegf Regulation Of Egr3 D Liu Et Almentioning
confidence: 90%
See 3 more Smart Citations